Sensors: Proceedings of the Second National Conference on Sensors, Rome 19-21 February, 2014 - Compagnone, D (Springer, 2015)
This book contains a selection of papers presented at the Second National Conference on Sensors held in Rome 19-21 February 2014. The conference highlighted state-of-the-art results from both theoretical and applied research in the field of sensors and related technologies. This book presents material in an interdisciplinary approach, covering many aspects of the disciplines related to sensors, including physics, chemistry, materials science, biology and applications